Porcine epidemic diarrhoea virus: a comprehensive review of molecular epidemiology, diagnosis, and vaccines - Song, Daesub; Park, Bongkyun (Virus genes, 2012)
The porcine epidemic diarrhoea virus (PEDV), a member of the Coronaviridae family, causes acute diarrhoea and dehydration in pigs. Although it was first identified in Europe, it has become increasingly problematic in many Asian countries, including Korea, China, Japan, the Philippines, and Thailand. The economic impacts of the PEDV are substantial, given that it results in significant morbidity and mortality in neonatal piglets and is associated with increased costs related to vaccination and disinfection. Recently, progress has been made in understanding the molecular epidemiology of PEDV, thereby leading to the development of new vaccines. In the current review, we first describe the molecular and genetic characteristics of the PEDV. Then we discuss its molecular epidemiology and diagnosis, what vaccines are available, and how PEDV can be treated.